Alloantigen-Induced Regulatory T Cells Generated in Presence of Vitamin C Display Enhanced Stability of Foxp3 Expression and Promote Skin Allograft Acceptance - Nikolouli, Eirini; Hardtke-Wolenski, Matthias; Hapke, Martin; Beckstette, Michael; Geffers, Robert; Floess, Stefan; Jaeckel, Elmar; Huehn, Jochen (Frontiers in Immunology, 2017)
Regulatory T cells (Tregs) are critical for the maintenance of immune homeostasis and self tolerance and can be therapeutically used for prevention of unwanted immune responses such as allotransplant rejection. Tregs are characterized by expression of the transcription factor Foxp3, and recent work suggests that epigenetic imprinting of Foxp3 and other Treg-specific epigenetic signatures genes is crucial for the stabilization of both Foxp3 expression and immunosuppressive properties within Tregs. Lately, vitamin C was reported to enhance the activity of enzymes of the ten eleven translocation family, thereby fostering the demethylation of Foxp3 and other Treg-specific epigenetic signatures genes in developing Tregs. Here, we in vitro generated alloantigen-induced Foxp3+ Tregs (allo-iTregs) in presence of vitamin C. Although vitamin C hardly influenced the transcriptome of allo-iTregs as revealed by RNA-seq, those vitamin C-treated allo-iTregs showed a more pronounced demethylation of Foxp3 and other Treg-specific epigenetic signatures genes accompanied with an enhanced stability of Foxp3 expression. Accordingly, when being tested in vivo in an allogeneic skin transplantation model, vitamin C-treated allo-iTregs showed a superior suppressive capacity. Together, our results pave the way for the establishment of novel protocols for the in vitro generation of alloantigen-induced Foxp3+ Tregs for therapeutic use in transplantation medicine.